2020
DOI: 10.1002/jbt.22665
|View full text |Cite
|
Sign up to set email alerts
|

Purpurin binding interacts with LHPP protein that inhibits PI3K/AKT phosphorylation and induces apoptosis in colon cancer cells HCT‐116

Abstract: Colorectal cancer (CRC) is the leading type of diagnosed cancer; globally, it resides in the fourth‐leading origin of cancer‐interrelated mortality in the globe. The treatment strategies were chemotherapy and potent radiotherapy. Although chemotherapy treatment can eliminate tumor cells, it remains with unnecessary toxic effects in cancer patients. Therefore, the identification of natural‐based compounds, which have selectively inhibiting target proteins with limited toxicity that can facilitate the therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…The phosphatidylinositol-3-kinase/protein kinase B (PI3K/AKT) signaling pathway is one of the most classical pathways involved in tumorigenesis ( Xie et al, 2019 ). Previous results indicated that cell cycle was arrested in the G0/G1 phase after improved expression of Lhpp, while reduction of Lhpp displayed the opposite results ( Li Z. et al, 2021 ). Therefore, the role of Lhpp is similar to that of tumor suppressor gene, indicating that CMF may inhibit the occurrence of CRA by regulating the expression of Lhpp.…”
Section: Discussionmentioning
confidence: 91%
“…The phosphatidylinositol-3-kinase/protein kinase B (PI3K/AKT) signaling pathway is one of the most classical pathways involved in tumorigenesis ( Xie et al, 2019 ). Previous results indicated that cell cycle was arrested in the G0/G1 phase after improved expression of Lhpp, while reduction of Lhpp displayed the opposite results ( Li Z. et al, 2021 ). Therefore, the role of Lhpp is similar to that of tumor suppressor gene, indicating that CMF may inhibit the occurrence of CRA by regulating the expression of Lhpp.…”
Section: Discussionmentioning
confidence: 91%
“…We revealed that DLGAP1-AS1 regulated several key cancer-related pathways, including PI3K/AKT. Interestingly, recent studies have reported that LHPP inhibits the PI3K/AKT signaling pathway in CRC [ 17 , 18 ]. We found that LHPP was expressed at lower levels in CRC tissues compared with NCTs based on multiple public CRC cohorts (Fig.S 10 A).…”
Section: Resultsmentioning
confidence: 99%
“…PI3K can directly cause phosphorylation of the downstream effector molecule Akt. When the PI3K/Akt pathway is activated, the Akt phosphorylation level increases, and when the PI3K/Akt pathway is inhibited, the Akt phosphorylation level decreases [ 30 32 ]. In this study, compared with the model group, the expression levels of PI3K, p-PI3K, Akt, and p-Akt proteins in the tumor tissues of the rats in each group were decreased in a dose-dependent manner after afuresertib intervention.…”
Section: Discussionmentioning
confidence: 99%